Attention Deficit Hyperactivity Disorder: Case Report and Literature Review on Vaginal Button Battery Insertion - Marzieh Azizi; Imaneh Ahmadi; Seyed Khosro Ghasempouri; Hamed Milani; Leila Monjazeb Marvdashti; Forouzan Elyasi (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: This study assesses the vaginal button battery insertion in a child with attention deficit hyperactivity disorder (ADHD).  Methods: For the literature review, online databases, such as Google Scholar and PubMed were searched with the following keywords: "Vaginal battery" OR "vaginal button battery" OR "vaginal battery insertion" AND "girl." The search process considered articles in English with no publication year limitation. The included studies were published from 2005 until 2023.  Case Presentation: We presented an eight-year-old, second-grade elementary school girl with ADHD and a history of methylphenidate consumption, referred to the general educational hospital in north Iran with the chief complaint of inserting a vaginal foreign body (VFB). On the night of the event. The child removed a small disc battery of her toys and inserted it into her vagina. Then, she told this to her parents and was referred to the hospital. The psychiatrist's assessment showed no psychiatric disorder, except for ADHD. The patient's abdomen was soft in physical examination and had a rebound tenderness complaint. Also, the entrance of the vagina was erythematosus, and vaginal discharge was seen. The primary assessment by pelvic radiography indicated a round button buttery in the upper segment of the rectum. In the surgery room, a gynecologist gently removed the button battery from the wall by rectal examination and milking from the upper under general anesthesia. The patient was febrile in the follow-up for 48 h and discharged with good general health without fever and severe psychiatric symptoms. In the review section of this study, case reports conducted regarding the insertion of battery in the vagina as a VFB in girls were searched and reported. Overall, 15 case reports were included in the literature review. Conclusions: Interdisciplinary cooperation among pediatric clinicians and gynecology specialists in dealing with cases of VFB associated with a wide range of emotional and behavioral disorders, such as ADHD should be considered.